Polyvinylidene fluoride based lightweight and corrosion resistant electromagnetic shielding materials. Issue 45 (20th May 2015) - Bhingardive, Viraj; Sharma, Maya; Suwas, Satyam; Madras, Giridhar; Bose, Suryasarathi
<x xml:space="preserve">Abstract</x> Various NixCo1−x alloys (with x varying from 0–60 wt%, Ni: nickel, Co: cobalt) were prepared by vacuum arc melting and mixed with polyvinylidene fluoride (PVDF) to design lightweight, and corrosion resistant materials that can attenuate electromagnetic radiation.